Post-Constitutional Court Ruling Number 168/PUU-XXI/2023: The Impact On Trade Unions And Worker Protection In Semiconductor Manufacturing - Edrick Edwardina Effendy; Mohammad Ahmad Eko Susilo (Faculty of Law, Universitas Pekalongan, 2025)
The Constitutional Court's Decision Number 168/PUU-XXI/2023 concerning the testing of the Job Creation Law has had a significant impact on various aspects of employment in Indonesia, including the protection of workers' rights and the role of trade unions in strategic industries. The purpose of this study is to analyze the impact of the Constitutional Court's decision Number 168/PUU-XXI/2023 on industrial relations between workers and entrepreneurs in the semiconductor manufacturing sector in Indonesia. This study uses a qualitative approach with a case study design to analyze the impact of the Constitutional Court's decision Number 168/PUU-XXI/2023 on labor unions and worker protection in the semiconductor manufacturing sector. The results of this study show that the Constitutional Court Decision Number 168/PUU-XXI/2023 provides more flexibility for employers in regulating employment, which has an impact on the tension of industrial relations between workers and employers, especially related to the increase in workload and reduced protection of workers' rights. This can be seen from data that shows a decline in workers' trust in trade unions and an increase in dissatisfaction with working conditions. Although unions have great potential in protecting workers' rights, they face major challenges in increasing member participation and their relevance to workers' needs. Employers who neglect worker welfare risk lower employee retention and productivity, while companies that care about worker welfare show more positive relationships with unions as well as better stability. The government also plays an important role in creating a balanced labor policy, prioritizing the welfare of workers without neglecting flexibility for employers